The Marketing Strategy of iPhone - Suwandhi, Daniel Ramadhan (2017)
The aim of this bachelor thesis is to understand how the American technological company Apple Inc. uses their marketing strategy to lure consumers to buy their products such as the iPhone, which is a really grossing product ever since its introduction back in 2007 and to identify the key crucial factors of success. Besides that, the image of Apple/iPhone in the Czech Republic and Indonesia will be analyzed and several recommendations for the future marketing strategy of Apple will be drafted. The introduction section will introduce to the reader the Apple’s history on its roots and how it became a global player in the mobile phone market. The product portfolio will be briefly described and commented on. The thesis is divided into two different parts, which is the theoretical part, followed by the practical part. Theoretical part will focus on marketing techniques and will explain definitions/ know-how. The practical part will show how Apple Inc. uses the marketing strategy in real life situations-analyzing the marketing strategy’s Pros and Cons and a draft of suggestions for improvement of the marketing strategy. Aside from that the methodology used would be a case study of the iPhone in the Czech market, which would use secondary (internet, book sources) data and the primary data, which is the questionnaire. The questionnaire will be targeted at 100 respondents using various question types and the method of the Likert Scale based on the decisive criteria used by consumers in the mobile phones product category.